Voice changes after surgically assisted rapid maxillary expansion - Erdur, Onur Erdem; YILMAZ, BERZA; YILMAZ, BERZA (My University, 2022)
Introduction: This study aimed to investigate voice changes in patients who had surgically assisted rapid maxillary expansion (SARME). Methods: Nineteen adult patients with maxillary transverse deficiency were asked to pronounce the sounds -[a], [epsilon], [(sic)], [i], [(sic)], [oe] [u], [y]- for 3 seconds. Voice records were taken before the expansion appliance was placed (T0) and 5.8 weeks after removal (T1, after 5.2 months of retention). The same records were taken for the control group (n = 19). The formant frequencies (F0, F1, F2, and F3), shimmer, jitter, and noise-to-harmonics ratio (NHR) parameters were considered with Praat (version 6.0.43). Results: In the SARME group, significant differences were observed in the F1 of [a] (P = 0.005), F2 of [epsilon] (P = 0.008), and [oe] sounds (P = 0.004). The postexpansion values were lower than those recorded before. In contrast, the F1 of [y] sound (P = 0.02), F2 of [u] sound (P = 0.01), the jitter parameter of [(sic)] and [i] sounds (P = 0.04; P = 0.002), and the NHR value of [epsilon] sound (P = 0.04) were significantly than the baseline values. In the comparison with the control group, significant differences were found in the F0 (P = 0.025) and F1 (P = 0.046) of the [u] sound, the F1 of the [a] sound (P = 0.03), and the F2 of the [epsilon] sound (P = 0.037). Significant differences were also found in the shimmer of [i] (P = 0.017) and [(sic)] (P = 0.002), the jitter of [epsilon] (P = 0.046) and [i] (P = 0.017), and the NHR of [i] (P = 0.012) and [(sic)] (P = 0.009). Conclusion: SARME led to significant differences in some of the acoustics parameters.